097 FACTORS ASSOCIATED WITH FALSE NEGATIVE CARDIOVASCULAR MAGNETIC RESONANCE PERFUSION STUDIES: A CE-MARC SUBSTUDY. (24th May 2013) - Plein, S; Kidambi, A; Sourbron, S; Maredia, N; Uddin, A; Motwani, M; Ripley, D P; Herzog, B; Brown, J M B; Nixon, J; Everett, C C; Greenwood, J P
Abstract : Background: Diagnosis of coronary ischaemia by perfusion cardiovascular magnetic resonance (CMR) has high sensitivity and specificity when using X-ray coronary angiography as the reference standard. Potential reasons for false negative perfusion CMR studies include suboptimal image quality, technical reasons, or the potential discrepancy between angiographic stenosis and detectable myocardial hypoperfusion. The rates at which these factors occur have not been specifically studied to date. The CE-MARC study prospectively enrolled 752 patients with suspected coronary artery disease, scheduled to undergo CMR, SPECT and X-ray coronary angiography. We assessed potential reasons for the false negative CMR perfusion studies within CE-MARC. Methods: All patients with significant coronary stenosis (≥70% stenosis of a first order coronary artery ≥2 mm diameter, or left main stem stenosis ≥50% as measured by quantitative coronary angiography (QCA)), who had a normal or probably normal CMR perfusion analysis from the original, blinded read were selected from the CE-MARC population. Patient and imaging characteristics were analysed. Myocardial perfusion reserve (MPR) was calculated offline (PMI v0.4) from CMR stress and rest perfusion images using the Fermi model, with arterial input defined in LV blood pool, and the whole mid-LV short axis myocardial slice used as tissue response. Results: 36 patients with a false-negative CMR result were identified (table 1 ). 1 patient had 'unusable' image quality grading, and was excluded from further analysis. 4 (11%) patients had images graded as 'poor quality.' 10 patients (29%) had inadequate hemodynamic response to adenosine (SBP decrease <10 mm Hg or heart rate increase <10 beats/min). 1 patient (3%) had angiographic 3-vessel disease, supporting balanced ischaemia. A further 6 patients (17%) had an adequate hemodynamic response but MPR <1.5, suggesting possible inadequate vasodilatation (in the absence of triple vessel disease). Of the remaining 14 patients, mean QCA diameter of culprit stenoses was 74%±12%, close to the angiographic cut-off of ≥70% for significant disease (figure 1 ). Conclusions: Of the many potential factors contributing to false negative CMR perfusion studies, over one third of false negative studies may have been related to lack of efficacy of pharmacological stress at the standard adenosine dose of 140 µg/kg/min. A substantial proportion of patients had coronary stenosis severity close to the angiographic cut-off of 70%, which may represent discordance between anatomical and functional assessment. Non-diagnostic image quality and three-vessel disease made a relatively small contribution to false-negative CMR studies.